Seismic and petrophysical data analysis for geological interpretation and subsurface modeling of Keva Field, onshore Niger Delta, Nigeria - Kembou Tsobin Evans; Olawale Olakunle Osinowo; Wasiu Odufisan; Bashir A. Koledoye; Yusuf Odusanwo; Tobechukwu Oluchukwu Ude-Akpeh; Glory Yenchek Tiele (Energy Geoscience)
This study integrates seismic and petrophysical data to evaluate the subsurface geology of the Keva Field, located onshore in the Niger Delta, with the objective of constructing a 3D geological model and estimating the recoverable hydrocarbon volumes. Seismic lines and well log data from six wells—KV-2, KV-3, KV-4, KV-5, KV-6, and KV-7—were utilized for the interpretation. The seismic profiles revealed that the KV-4 well is the only well drilled on the up-thrown side of a significant horst fault block, bounded by four major normal faults, while all the other wells penetrated the downthrown side. Petrophysical analysis identified three key reservoirs, C500, D200, and E900, which exhibit excellent reservoir quality with high net-to-gross ratios, good porosity, and high hydrocarbon saturation. The identified depositional environments are tidal- and fluvial-dominated shoreface settings, with sheet sands deposited in distributary splay systems. The C500, D200, and E900 reservoirs have Gas Initially in Place (GIIP) values of 156.37, 28.44, and 27.89 BSCF, respectively, with corresponding Estimated Ultimate Recovery (EUR) values of 104.77, 19.06, and 18.69 BSCF, respectively. The Stock Tank Original Oil in Place (STOOIP) values are 24.43, 91.29, and 86.41 MMSTB, with EURs of 7.32, 27.4, and 25.92 MMSTB, respectively. The combined GIIP is 212.72 BSCF with EUR of 142.52 BSCF, while the total STOOIP is 202.13 MMSTB with a recoverable volume of 60.64 MMSTB. The reservoirs present an average porosity of 22.62 %, with gas saturation of 84.66 % and oil saturation of 73 %. The evaluated reservoir qualities suggest high potential for optimized hydrocarbon production.